Diallel-cross analysis of grain yield and stress tolerance-related traits under semi-arid conditions in Durum wheat (Triticum durum Desf.) - HANNACHI Abderrahmane, FELLAHI Zine El Abidine, BOUZERZOUR Hamenna and BOUTAKRABT Ammar (Electronic Journal of Plant Breeding, 2013)
Half-diallel analysis with six genotypes of durum wheat was conducted for grain yield, yield components and agronomictraits related to abiotic stress tolerance. Aim of this study is to identify best parents for hybridization. Cultivar GuemgoumRkhem proved to be best general combiner for number of days to heading, straw yield, plant height and thousand-kernelweight. Gaviota durum was best combiner for number of grains per spike, and cultivar Ofanto for Chlorophyll content andharvest index. Waha proved to be a poor general combiner for flag leaf area, straw yield, plant height and thousand-kernelweight. Mexicali75/Guemgoum Rkhem cross is best suited to improve earliness, straw yield, plant height, and grain yield.Narrow-sense heritability was low for grain yield. Waha//Zenati Bouteille/Flamingo and Waha/ Guemgoum hybridsshowed significant mid-parent heterosis for grain yield.